An analysis of Latin American Scientific Production on Teacher Stress (2010 - 2018) - Luy-Montejo, Carlos Augusto Luy-Montejo (2019)
The purpose of this research was to evaluate the scientific production on teacher stress. It is a cross-sectional descriptive study of articles published in journals indexed in the SciELO collection between 2010 and 2018. An estimate of publications per year, journals, institutional affiliations and publication topics was analyzed. It was found that between the aforementioned years, 60 articles on the subject have been published, out of which the years of greatest production fluctuate between 2014 and 2018. The main journals that published articles on this topic are: Research News in Education, Uninorte Health Magazine and the Magazine of Medical Sciences of Pinar del Río in Cuba. In addition, Brazil, Colombia and Cuba have the institutional affiliations with the highest number of published articles. We can conclude that teacher stress as a research variable has been studied gradually in Latin American countries; however, it is necessary to continue strengthening these studies in other databases.